ANALISIS KESULITAN GURU SD DALAM MENGEMBANGKAN INSTRUMEN PENILAIAN MATEMATIKA BERBASIS HOTS - Helmon, Arnoldus; Lasa, Laurensius; Fabianus Hadiman Bosco (PGSD UNIKA SANTU PAULUS RUTENG, 2024)
21st century learning requires teachers to develop HOTS-based learning assessment. However, so far, teachers still experience difficulties in developing these assessment instruments. This study aims to describe the types and factors causing elementary school teachers' difficulties in developing HOTS-based assessment instruments. For this purpose, qualitative research was conducted involving 4 elementary school teachers as research subjects. Data were collected through interviews and analyzed through data reduction, data display and conclusion drawing. The results showed that the difficulties experienced by elementary school teachers in developing HOTS-based assessment instruments include: difficulties in determining operational verbs, formulating HOTS-based statements and questions, difficulties in formulating HOTS question statements and questions, and compiling HOTS-based assessment rubrics. Factors causing these difficulties include: teachers' understanding of HOTS questions is not sufficient, teachers experience time constraints, teachers are not used to preparing HOTS questions, lack of training and socialization, and students' understanding of mathematics concept is still weak